2020
DOI: 10.3390/cancers12092632
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Respiratory Defect Enhances Hepatoma Cell Invasiveness via STAT3/NFE2L1/STX12 Axis

Abstract: Mitochondrial respiratory defects have been implicated in cancer progression and metastasis, but how they control tumor cell aggressiveness remains unclear. Here, we demonstrate that a mitochondrial respiratory defect induces nuclear factor-erythroid 2 like 1 (NFE2L1) expression at the transcriptional level via reactive oxygen species (ROS)-mediated STAT3 activation. We identified syntaxin 12 (STX12) as an effective downstream target of NFE2L1 by performing cDNA microarray analysis after the overexpression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Moreover, a distinct pool of STAT3 resides in the mitochondria and is responsible for the control of ETC, modulation of ROS production, Ras transformation, cellular growth, and protection from ischemia/reperfusion injuries through the regulation of the mitochondrial permeability transition pore (MPTP) [ 77 ]. Very recently, Lee et al elucidated a role in hepatoma cell invasiveness of ROS-induced STAT3 activation, which in turn promoted Nrf2 transcription and syntaxin 12 expression [ 78 ].…”
Section: Mitochondrial Ros Involvement In Cancermentioning
confidence: 99%
“…Moreover, a distinct pool of STAT3 resides in the mitochondria and is responsible for the control of ETC, modulation of ROS production, Ras transformation, cellular growth, and protection from ischemia/reperfusion injuries through the regulation of the mitochondrial permeability transition pore (MPTP) [ 77 ]. Very recently, Lee et al elucidated a role in hepatoma cell invasiveness of ROS-induced STAT3 activation, which in turn promoted Nrf2 transcription and syntaxin 12 expression [ 78 ].…”
Section: Mitochondrial Ros Involvement In Cancermentioning
confidence: 99%
“…To monitor mitochondrial respiratory activity, OCR was measured using Seahorse XF24 analyzer (Seahorse Bioscience Inc., MA) as described in the previous report [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another group led by Yoon reported that Nrf1 acts as one of the most responsive genes when the mitochondrial respiratory chain is damaged (70,71). These putative effects of Nrf1 prompt us to gain insights into its redox regulation for mitochondrial homeostasis, because this organelle is a main resource of intracellular ROS production.…”
Section: Nrf1 Serves As An Indispensable Redox-determining Factor In ...mentioning
confidence: 99%